Optical Harmonic Generation in 2D Materials. (16th December 2021) - Khan, Ahmed Raza; Zhang, Linglong; Ishfaq, Kashif; Ikram, Adeel; Yildrim, Tanju; Liu, Boqing; Rahman, Sharidya; Lu, Yuerui
Abstract: 2D materials are emerging as ideal candidates for fundamental investigations and new technologies due to their unique optoelectronic properties. Giant nonlinear susceptibility and perfect phase matching in 2D materials lead to extraordinary nonlinear light matter interactions, thus enabling several potential applications and fundamental scientific discoveries in nonlinear optics. For instance, second harmonic generation in 2D materials play an important role in optical devices such as, lasers, tunable waveguides, electro‐optic modulators, and switches. This review will discuss optical harmonic generation (OHG) processes, various characterization modes, and tuning techniques in 2D materials. The future prospectives for OHG in 2D materials is discussed. The extremely promising attributes of combining nonlinear optics and 2D materials is becoming a highly important multidisciplinary field. Abstract : Optical harmonic generation (OHG) is reviewed in 2D materials. First, 2D materials are introduced with respect to their optical harmonic properties. Second, various types of characterization modes and tuning techniques in 2D materials are reviewed using their OHG properties. Finally, a review of 2D materials based device applications is presented based on their OHG properties.